Morphodynamic modeling of the Ancão Inlet, South Portugal - Bertin, X. (2009)
Morphodynamic modeling systems increasingly appear as valuable tools to understand the dynamics of coastal systems, including mixed-energy tidal inlets, driven by the combined action of tides and waves. This study aims at: 1) applying and validating a morphodynamic modeling system to a rapidly evolving tidal inlet and 2) verifying both qualitatively and quantitavely the ability of the morphodynamic modeling system to simulate the development of the inlet's main features. The MORSYS2D morphodynamic modeling system is applied to the Ancão Inlet (South Portugal), just after its relocation in August 1997. The relocation and the first stages of the inlet development were monitored in the scope of the EU project INDIA, which provided a large database of tidal, wave and bathymetric data. The first step of the present study consists on a fine calibration of the morphodynamic modeling system using the INDIA data. The model/data comparison shows that the modeling system was able to reproduce well wave heights, elevations and current velocities, with root mean square errors of 0.25 m, 0.065 m and 0.12 m/s, respectively. The morphological evolution of Ancão Inlet is then simulated over the period August 1997-January 1999, starting at the inlet relocation. Model predictions were compared to the bathymetric surveys available over the simulated period. Model/data comparison demonstrates that the model is able to reproduce the development of the main features of the Ancão Inlet. From a quantitative viewpoint, the model was also able to reproduce the development of the inlet's cross-section, characterized by faster growths during fair weather conditions. Finally, this study also provides additional insight regarding on the dynamics of mixed-energy (tide, waves) tidal inlets.